Peran Pola Asuh Orang Tua Terhadap Fungsi Eksekutif Pada Individu Dewasa Awal : Peran Pola Asuh Orang Tua Terhadap Fungsi Eksekutif Pada Individu Dewasa Awal - Azima, Siti Lailan; Arpandy, Ghea Amalia; Fitriah, Aziza (Psikodinamika: Jurnal Literasi Psikologi, 2025)
Executive function is a cognitive process in everyday life such as making a decision in solving problems in the early adult phase. The development of executive function can be influenced by the role of the family. Parents have a major role in the growth and development of children, especially in cognitive development from early childhood to adulthood. This study aims to understand the relationship between authoritarian, democratic and permissive parenting on executive function in early adult individuals. The method utilized is a quantitative approach with a correlational design. The measuring instruments used were the parenting scale and the executive function scale. Sampling used purposive sampling method and involved 116 individuals aged 18 to 25 years who lived with their parents from childhood until now in Banjarmasin City. Data analysis in this study used Pearson's Product Moment and Spearman Rho correlation tests. The results of this study prove that there is a correlation between authoritarian, democratic, and permissive parenting patterns and executive function in early adults. As a parent, you should be able to choose a good parenting pattern for the development of executive function from infancy to adulthood before applying it in parenting. Keywords: early adulthood, executive function, parenting style